Store depletion induces Gαq-mediated PLCβ1 activity to stimulate TRPC1 channels in vascular smooth muscle cells - Shi, Jian (2016)
Depletion of sarcoplasmic reticulum (SR) Ca2+ stores activates store-operated channels (SOCs) composed of canonical transient receptor potential (TRPC) 1 proteins in vascular smooth muscle cells (VSMCs), which contribute to important cellular functions. We have previously shown that PKC is obligatory for activation of TRPC1 SOCs in VSMCs, and the present study investigates if the classic phosphoinositol signaling pathway involving Gαq-mediated PLC activity is responsible for driving PKCdependent channel gating. The G-protein inhibitor GDPb- S, anti-Gαq antibodies, thePLCinhibitorU73122, and the PKCinhibitorGF109203Xall inhibited activation ofTRPC1 SOCs, and U73122 and GF109203X also reduced storeoperated PKC-dependent phosphorylation of TRPC1 proteins. Three distinct SR Ca2+ store-depleting agents, 1,2-bis(2-aminophenoxy)ethane-N,N,N9,N9-tetraacetic acid acetoxymethyl ester, cyclopiazonic acid, and N,N,N9,N9- tetrakis(2-pyridylmethyl)ethane-1,2-diamineed,inducedtranslocations of the fluorescent biosensor GFP-PLCd1-PH from the cell membrane to the cytosol, which were inhibited by U73122. Knockdown of PLCβ1 with small hairpin RNA reduced both store-operated PLC activity and stimulation of TRPC1 SOCs. Immunoprecipitation studies and proximity ligation assays revealed that store depletion induced interactions betweenTRPC1andGαq, andTRPC1and PLCβ1. Wepropose a novel activation mechanismforTRPC1SOCs in VSMCs, in which store depletion induces formation of TRPC1-Gαq-PLCβ1 complexes that lead to PKC stimulation and channel gating.